(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed to evaluate the effectiveness of a blended case-based learning and lecture-based learning method compared with the traditional lecture-based learning method in the basic sciences module, and to assess first-year dental students’ case-based learning self-directed learning skills and satisfaction with case-based learning sessions. Methods: In this quasi-experimental pretest-posttest study, the sample comprised 76 first-year dental students at Nguyen Tat Thanh University. Outcomes included lecture-based learning (Pretest) scores, case-based learning (Posttest) scores, case-based learning self-study scores, and case-based learning session evaluation scores. Results: Student rating consistency was 81.3%. The intraclass correlation coefficient (ICC) was 0.80, indicating good reliability. The mean case-based learning score was 8.7 ± 0.7, increased by 2.0 ± 1.7 points compared with the mean lecture-based learning score of 6.7 ± 1.7 (p < 0.001). Overall, 77.6% of students achieved higher grades in case-based learning than in lecture-based learning. The mean case-based learning self-directed learning skills score was 6.7 ± 1.7, corresponding to a moderate grade (3.9 ± 1.2). The mean student satisfaction score across the six case-based learning sessions was 4.7 on a 5-point Likert scale, indicating a high level of satisfaction. Conclusion: Case-based learning demonstrated superior effectiveness to traditional lecture-based learning in the basic sciences module. These findings provide additional scientific and practical support for implementing, scaling up, and standardizing case-based learning in the dental training program.